SOME ASPECTS OF THE CONCEPT OF SPIRITUAL RENEWAL IN UZBEKISTAN - Nurmuhamedzhanov Ahmadjon Mahmudovich (Journals Park Publishing, 2023)
This article focuses on the concept of "spiritual renewal" and its essence. The spiritual life of the community focuses on spiritual activities, and spiritual relationships are widely covered in the article. The article also talks about spiritual values, the concept of spiritual renewal and its meaning.
Keywords: concept of spirituality, spiritual life of society, spiritual renewal, spiritual activity, spiritual relations, spiritual needs, spiritual interests.